Biogeochemical Transformations in the Baltic Sea Observations Through Carbon Dioxide Glasses - Schneider, Bernd (Springer Oceanography, 2018)
This book provides a comprehensive review of the biogeochemistry in the Baltic Sea. It is based on the fact that biogeochemical processes that are relevant for the ecological state of the Baltic Sea (and other sea areas), are all in some way related to the production and mineralization of organic matter (biomass) and thus are associated with the consumption or release of CO2. The significant progress with regard to our chemical analytical capabilities concerning the marine CO2 system has facilitated new approaches to study the Baltic Sea biogeochemistry, in particular with regard to a quantitative process understanding. To demonstrate this, the authors present the fundamentals of the marine CO2 system in a theoretically sound, but still intelligible way. This is followed by a comprehensive presentation of our current knowledge about the CO2 system in the Baltic Sea and the implications for our understanding of biogeochemical processes such as production/mineralization of organic matter and the stoichiometry involved, nitrogen fixation, denitrification, and phosphate transformations at varying redox conditions. Finally, the CO2 gas exchange balance and related problems such as acidification are addressed.